Effect of Andrographis paniculata a Phytobiotic on Consumption, Feed Conversion and Mojosari Duck Egg Production - Yulianti , Dyah Lestari; Trisunuwati, Pratiwi; Sjofjan, Osfar; Widodo, Eko (International Journal of Poultry Science, 2015)
The aim of this research was to investigate the effect of Andrographis paniculata leaf powder as a phytobiotic on feed consumption, feed conversion and egg production of the Mojosari duck (Mojosari anas plathryncos). One-hundred 24-month-old Mojosari ducks were given basal feed with different concentrations of Andrographis paniculata leaf powder as a feed additive. Experiments were arranged with a completely random design, with five leaf powder concentrations, each replicated four times; A. paniculata leaf powder was added to rations in the following concentrations: 0% (P0), 0.2% (P1), 0.4% (P2), 0.6% (P3) and 0.8% (P4). Data was analyzed using analysis variants and if there was a difference between treatments, those data were further subjected to a least significant difference test; variables included feed consumption, daily egg production and feed conversion. Results showed that A. paniculata leaf powder significantly affected (p<0.05) feed conversion and egg production of Mojosari ducks. However, A. paniculata leaf powder had no significant effect (p>0.05) on feed consumption. Average feed consumption per treatment (P0, P1, P2, P3, or P4) was 136.77, 137.82, 135.8, 139.47 and 138.97 g/bird/d, respectively. Average feed conversion values were 9.35 (P0), 5.92 (P1), 4.93 (P2), 7.01 (P3) and 13.50 (P4) and average egg production percentage per treatment was 23.18% for P0, 33.73% for P1, 42.22% for P2, 28.25% for P3 and 14.61% for P4. It was concluded that 0.4% A. paniculata leaf powder was optimal for its phytobiotic actions on Mojosari ducks.